Honeycomb boron carbon nitride as high-performance anode material for li-ion batteries - Karbhal, Indrapal; Chaturvedi, Vikash; Patrike, Apurva; Yadav, Poonam; Shelke, V, Manjusha (ChemNanoMat, 2022)
3D Porous carbon-based materials are well known for their excellent mechanical and electrochemical properties for various energy storage applications including Li-ion Battery (LIB) anodes. However, their commercial application is limited due to their low theoretical specific capacity. Heteroatom doping in carbonaceous networks proved an efficient way to modify the surface properties, which considerably improves the Li intake capacity and Li diffusion in porous carbon materials. In this work, we have synthesized 3D honeycomb boron carbon nitride (HBCN) from boric acid, glucose, and cyanamide. Silica nanoparticles (SiO2 NPs) are used as structure-directing agents to replicate well-organized honeycomb structures. HBCN possesses a high specific surface area (SSA) of similar to 597 m(2) g(-1), with a uniform porosity distribution, low charge transfer resistance, and steady Li flux. When analyzed as an anode material for LIB, HBCN demonstrated an excellent specific capacity of similar to 652 mAhg(-1) and 408 mAhg(-1) at an input current density of 100 mAg(-1) and 1 Ag-1 respectively and an energy density of 227 Wh kg(-1) at 1 C rate in a full cell LIB. These results indicate that the doping of B and N hetero atoms is significantly advantageous for LIBs application.
Keywords: 3D-Architecture; Heteroatom Doping; High-Performance Anode; Honeycomb boron carbon nitride (HBCN); Li-ion battery